Evaluation of Acute Dermal Toxicity of Hibiscus Leaves as Simplicial Ointment on Albino Rats - Saputra, Made Gede Adi Surya; Sudira, I Wayan; Samsuri, Samsuri; Merdana, I Made; Dharmayudha, Anak Agung Gde Oka; Sudisma, I Gusti Ngurah (Jurnal Medik Veteriner, 2023)
Hibiscus is a plant that has been shown to contain substances that may be used as sunscreen to protect the skin from UV radiation. In terms of their potential as sunscreens, flavonoids, tannins, and quinone chemicals are crucial because they are antioxidants that can reduce the negative effects of UV radiation and boost photoprotective activity. This study aimed to investigate the acute dermal toxicity potential of hibiscus leaves simplicial ointment 40% on female albino rats. The evaluation method refered to The OECD Guideline for Testing of Chemicals – No. Test: 402, Acute Dermal Toxicity-Fixed Doses Procedure. Based on the Globally Harmonized System compared to this study reported that acute dermal median lethal dose (LD50) was > 2000 mg/kg. It can be concluded that hibiscus leaves simplicial ointment 40% has safe to apply topically and doesn't produce acute skin toxicity.